THE INDONESIAN SHARIA BANK PLAYS A CRUCIAL ROLE IN SUPPORTING THE SHARIA ECONOMIC COMMUNITY PROGRAM IN TIRTANADI VILLAGE - Sapwan, Muhammad (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This article discusses the MES organization together with the government and Bank Syariah Indonesia launching the MES program, namely rose mas in NTB with the aim of growing the community's economy and eradicating mosque-based loan sharks. This type of research uses descriptive qualitative research, which is classified as field research. The data collection techniques used in this research are observation, interviews and documentation techniques. Data analysis techniques use stages of data reduction, data presentation and data verification. The results of this research show that Bank Syariah Indonesia together with the MES Program is able to build a quality economy by increasing economic growth rates by opening employment opportunities by offering businesses from the capital provided by Bank Syariah Indonesia through the MES program implemented in Dasan Gerung, Tirtanadi Village to reduce unemployment rates and by The implementation of the MES program can reduce users of loan shark services in Dasan Gerung, Tirtanadi Village.